Standing Biomass and Carbon Stocks in Trees Outside forests of Kurnool District, Andhra Pradesh, India - Ravi Prasad Rao, B.; Srinivasa Rao, V.; Prasad, K.; Ramesh, M.; Veeranjaneyulu, D.; Thulsi Rao, K. (Indian Forester, 2013)
The study was aimed to estimate standing biomass and carbon stocks in linear, scattered and block structures of trees outside forests through non-destructive method in Kurnool district of Andhra Pradesh. A total of 45.65 ha area was sampled in the district for this purpose. The study recorded a total of 19 species from linear plots, 35 species from scattered and 8 species in blocks with mean stem density of 18.2, 100.5 and 153.8 individuals’ ha-1 respectively and their respective mean basal area is 17.45, 1.48 and 26.58 m2ha-1. The growing stock density is 13.59, 57.94 and 15.49 m3 for linear, scattered and block structures respectively and standing biomass density values are 99.14Â±216.48 Mg ha-1, 5.73Â±7.37 Mg ha-1 and 105.16Â±125.43 Mg ha-1 for the same. The carbon stocks in linear structure is 47.09Â±102.8 Mg ha-1; scattered structure 2.72Â±3.50 Mg ha-1 and block structure 49.95Â±59.58 Mg ha-1. The girth class distribution shows that in linear, scattered and block structure >150 cm GBH class contributes higher values of growing stock, standing biomass and carbon stocks.